First principle issue of functional rehabilitation identification of the traditional channels of zhenjiu therapy as the problem of functional rehabilitation - Makats, V. G.; Makats, E. F.; Makats, D. V.; Makats, D. V.; Makats, O. D. (Journal of Education, Health and Sport, 2015)
Makats V. G., Makats E. F., Makats D. V., Makats D. V., Makats O. D. First principle issue of functional rehabilitation identification of the traditional channels of zhenjiu therapy as the problem of functional rehabilitation = Перше принципове питання функціональної реабілітації ідентифікація акупунктурных каналів чжень-цзю терапії як проблема функціональної реабілітації. Journal of Education, Health and Sport. 2015;5(8):367-384. ISSN 2391-8306. DOI10.5281/zenodo.29590 http://dx.doi.org/10.5281/zenodo.29590 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A367-384 https://pbn.nauka.gov.pl/works/614335 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.06.2015. Revised 24.08.2015. Accepted: 24.08.2015. First principle issue of functional rehabilitation IDENTIFICATION OF THE TRADITIONAL CHANNELS OF ZHENJIU THERAPY AS THE PROBLEM OF FUNCTIONAL REHABILITATION Перше принципове питання функціональної реабілітації ІДЕНТИФІКАЦІЯ АКУПУНКТУРНЫХ КАНАЛІВ ЧЖЕНЬ-ЦЗЮ ТЕРАПІЇ ЯК ПРОБЛЕМА ФУНКЦІОНАЛЬНОЇ РЕАБІЛІТАЦІЇ 1V. G. Makats, 2E. F. Makats, 1D. V. Makats, 3D. V. Makats, 4O. D. Makats 1В. Г. Макац, 2Е. Ф. Макац, 1Д. В. Макац, 3Д. В. Макац, 4О. Д. Макац 1Vinnitsa institute of the University “Ukraine” 2Vinnytsia National medical university named after Pirogov M.I. 3State enterprise of the Ukrainian scientific-research institute of transport medicine of HM of Ukraine 4Ukrainian Research Center activation therapy NADIYA 1Вінницький інститут Університету "Україна" 2Вінницький НМУ ім. М.І.Пирогова 3Державне підприємство Український НДІ медицини транспорту МОЗ України 4Український Науково-дослідний центр біоактиваційної терапії НАДІЯ Abstract The methodology of identification of the traditional acupunctural channels has no analogues. For the first time in the world practice it became possible to prove their biophysical reality and direct relation to vegetative homeostasis. Key words: Zhenjiu therapy, acupunctural channels, functional-vegetative system of the human. Реферат Методологія ідентифікації традиційних акупунктурних каналів не має аналогів. Вперше в світовій практиці появилась можливість доказати їх біофізичну реальність і безпосереднє відношення до вегетативного гомеостазу. Ключові слова: Чжень-цзю терапія, акупунктурні канали, функціонально-вегетативна система людини, функціональна реабілітація. Реферат Методология идентификации традиционных акупунктурных каналов не имеет аналогов. Впервые в мировой практике появилась возможность доказать их биофизическую реальность и непосредственное отношение к вегетативному гомеостазу. Ключевые слова: Чжень-цзю терапия, акупунктурные каналы, функционально-вегетативная система человека.